Musculoskeletal, hearing and skin problems related to playing the instrument - Aleksandra Jacukowicz; Agata Wężyk (Nofer Institute of Occupational Medicine, 2018)
Background Physical demands, exposure to noise and intense contact of skin with musical instruments - inevitable in musicians' job - influence the development of musculoskeletal, hearing and skin problems. This paper aims at identifying playing-related health problems among Polish musicians and potential differences in this regard between students and professional musicians. Material and Methods This questionnaire study involved 255 musicians who volunteered to participate - 104 students and 151 professional musicians having music education. The study sample included 61% of women. Mean age of the participants equaled 31 years old, mean playing experience - 23 years old. Results From 10% to 79% (depending on the affected body part) of the studied musicians experienced musculoskeletal problems. Hearing (41% - tinnitus; 43% - hearing impairment and 52% - hyperacusis) and skin problems (69% - callosities, 58% - abrasions and 26% - allergic reactions) were reported less frequently and were assessed as less severe than musculoskeletal symptoms. The studied professionals assessed their hearing problems (hyperacusis, hearing impairment and tinnitus) as significantly more severe than reported by students. Young musicians, in turn, experienced more severe abrasions than the studied professional musicians. We found no significant differences between students and professionals as regards their musculoskeletal problems. Conclusions Playing-related health risks translate into relatively high prevalence of musculoskeletal as well as hearing and skin problems among musicians. Hence, it is essential for future studies to search for risk factors for these health problems as well as effective corrective and therapeutic measures. Med Pr 2018;69(4):383-394